Reactivity comparison of Amadori rearrangement product formation of glycine, diglycine, and triglycine in a competing Maillard system - Yue Luo; Baojun Xu; Shiming Li; Chi-Tang Ho (Journal of Food Bioactives, 2022)
Although a certain number of amino acid-Amadori rearrangement products (ARPs) have been studied, there is still a lack of knowledge of small peptide-ARPs. Filling the gap should be a great step in the potential usage of ARP as future flavor additives. This study illustrated that small peptides (diglycine and triglycine) exhibited better relative reactivity of ARP formation than an amino acid (glycine) at relatively low temperature such as 80 and 100 ℃ and in a wide range of pH from acidic to neutral conditions, but the result reversed at high temperatures for severer instability of small peptide-ARPs. The relative reactivity of ARP formation of amino compounds in a competing Maillard systems results from dynamic systems with various factors including the chemical characterization and composition of intrinsic reactants, and parameters of matrix conditions like pH, temperature and thermal treatment time among others. Further research should be conducted to investigate peptide-ARPs, for which are ubiquitous in real food systems and worth to pay more attention.